2016
DOI: 10.1063/1.4952377
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of monolayer MoS2 in enhanced photocatalytic performance of hybrid MoS2/SnO2 nanocomposite

Abstract: The enhanced photocatalytic performance of various MoS2-based nanomaterials has recently been observed, but the role of monolayer MoS2 is still not well elucidated at the electronic level. Herein, focusing on a model system, hybrid MoS2/SnO2 nanocomposite, we first present a theoretical elucidation of the dual role of monolayer MoS2 as a sensitizer and a co-catalyst by performing density functional theory calculations. It is demonstrated that a type-II, staggered, band alignment of ∼0.49 eV exists between mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…4b) by the three-dimensional charge density difference where , , and are the charge densities of the hybrid, monolayer ZrS 2 , and ring B 20 cluster in the same configuration, respectively. Owing to the non-covalent interaction, a very interesting charge redistribution at the hybrid ZrS 2 /B 20 can be clearly seen, which is different from those of the MoS 2 /SnO 2 and Ag 3 PO 4 /GR heterostructures [33, 35]. A strong charge accumulation (blue part in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…4b) by the three-dimensional charge density difference where , , and are the charge densities of the hybrid, monolayer ZrS 2 , and ring B 20 cluster in the same configuration, respectively. Owing to the non-covalent interaction, a very interesting charge redistribution at the hybrid ZrS 2 /B 20 can be clearly seen, which is different from those of the MoS 2 /SnO 2 and Ag 3 PO 4 /GR heterostructures [33, 35]. A strong charge accumulation (blue part in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It has been demonstrated that non-covalent modification by graphene or monolayer MoS 2 can extend the absorption edge of semiconductors (like TiO 2 , AgPO 4 and SnO 2 ) to the vis-light region [33, 35, 36]. Similarly, coupling fullerene with photocatalysts is also an effective strategy to enhance the light absorption [34].…”
Section: Resultsmentioning
confidence: 99%
“…So, it can improve the interfacial activity and electron transport kinetics. [36] The interplanar distances of 0.37 nm can be identified to (110) planes of tetragonal rutile SnO 2 and lattice fringes with spacing of 0.27 nm corresponds to (100) plane of hexagonal MoS 2 in 5 % MS/SON in Figure 2(d), [27] the DFT calculation results are 3.6 Å of SnO 2 110 and 2.6 Å of MoS 2 100 crystal face, [30] respectively. Besides, the particle size distribution of 5 % MS/SON is not uniform, with the diameter ranging from 22 to 30 nm, and the average particle size is about 26 nm from Figure 2(c) and (d), which is almost consistent with DFT and XRD results.…”
Section: Physical Structurementioning
confidence: 99%
“…In consideration of the large specific surface area of the layered materials and good optical response of MoS 2 and based on density functional theory (DFT) calculation. [30] We envisage combining the granular SnO 2 with MoS 2 not only to expand the specific surface area of the composite but also make full use of the optical performance of MoS 2 . Thus, it can increase the surface adsorption sites to adsorb more CO 2 molecules, we synthesized the two-dimensional nanostructure MoS 2 loaded on SnO 2 nanoparticles (labeled as MS/SON) by two-step processes of facile hydrothermal and pyrolysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical 2D metal sulfide photocatalyst, molybdenum disulfide (MoS 2 ) with a layered structure has been studied extensively [126,127]. Hou et al [128] presented the fabrication of 2D porous g-C 3 N 4 nanosheets/nitrogen-doped graphene/layered MoS 2 (CNNS/NRGO/MoS 2 ) ternary nanocomposites.…”
Section: D/2dmentioning
confidence: 99%